Diverse Legal Significance of a Document in Byzantine Private Law - Tamara M. Matović (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2017)
Byzantine, Graeco-Roman, law is the organic continuation of Roman law. However, the legal system itself, and many legal institutions in it, had gone through certain evolution. In this article, by researching Greek acts conserved in various monastic arhives, and confronting them with stipulations in the Byzantine law codes, we question the issues of consensuality of a contract, form of a legal deed, and acquisation of a real right in Byzantine private law. The nature of contracts in Byzantine law has not been sufficiently studied. Richful theoretical studies had been written in regards to the contract of purchase in Roman and Justinians law, however various and sometimes confronting information from the later Greek codes did not give definite answers to this question. Byzantine codices on this theme encompass already familiar stipulations and legal institutes. The attention of the lawgiver was on the notary system, on the mechanism which produced a written instrument. We believe that the issue of the παράδοσις δι̉ ἐγγράφου was not sufficiently highlighted in the field of Byzantine studies mostly due to the lack of information in the sources. However, when regarding the Athonite documents, it can be seen that the formulae describing the act of law transfer could be concidered as a relevant material to comment on this legal institute.